Prevalence of dyslipidemias in human immunodeficiency virus-infected patients with and without antiretroviral therapy. - Chaudhary, Rabail; Farhan, Ahmed; Muhammad Zeehan; Tahir, Mohammad Awais; Kanwal , Saira (International Journal of Endorsing Health Science Research, 2022)
Background: Disturbances in the lipid profile and dyslipidemia are prevalent among human immunodeficiency virus (HIV) patients. Furthermore, long-term use of antiretroviral therapy (ART) exacerbates the condition. Data on lipid profile abnormalities among patients receiving highly active antiretroviral treatment in Pakistan are very limited. The present study aims to assess the frequency of dyslipidemia and lipid concentrations among HIV-infected patients receiving active art in comparison to those not receiving any treatment. Methodology: A cross-sectional study was carried out at the HIV clinic of Pakistan Institute of Medical Sciences, Islamabad, from January to July 2018. A total of 100 HIV-infected patients aged 13 to 60 years who gave consent and fulfilled the inclusion criteria were enrolled in the study via non-probability consecutive sampling. All patients who had positive HIV antibodies via the Elisa process were considered positive. Samples were examined for fasting lipids by using standard laboratory procedures. Results: The patients' mean age was 32.7 ± 13.4 ranging between 13-60 years. The total patient population consisted of 71% males and 29% females with a mean BMI of 21.1 ± 3.4 kg/m2. Out of 100, 38% of the study patients had dyslipidemia. The observed prevalence rate of hypertriglyceridemia, hypercholesterolemia, low HDL-C, and high LDL-C were 21%, 30%, 20%, and 16%, respectively. None of the factors were found in significant association with abnormal lipid parameters except the older patients (41-60 years) were at higher risk of hypercholesterolemia [aOR 0.15 (95% CI 0.02-0.92); p=0.04] than the counterpart. Conclusion: The study has demonstrated that a higher percentage of HIV-infected patients have concomitant dyslipidemia with or without art treatment.